REPEATED CRIMES: LEGAL ASPECTS OF CRIMINAL RESPONSIBILITY - Suyunova Dilbar Joldasbaevna, (Scholar Express Journals, 2022)
The general legal principle “Non bis in idem” (“No one can be held twice responsible for the same crime”) is reflected in the Criminal Code of the Republic of Uzbekistan, but it is not used professionally enough, since the interpretation of this principle in the norms of the criminal law is different. The regulation in the law of such signs of the commission of a crime as “repeated crimes”, “commission of a crime again”, “dangerous recidivist”, “especially dangerous recidivist”, in our opinion, somewhat narrows the content of this principle, which, of course, affects the guarantees of ensuring the rights and freedoms of citizens . The objectives of the study in this article are to analyze the criminal law norm relating to repetition in the commission of a crime, to compare the requirements of Article 32 of the Criminal Code of the Republic of Uzbekistan with the generally recognized principle of “Non bis in idem”, the legal assessment of the plurality of crimes from the position of the criminal law doctrine, the development of some proposals concerning amendments to the current criminal legislation
Keywords: Criminal legal norm; the principle of justice; fair punishment